KEBIJAKAN FERTILITAS SEBAGAI INSTRUMEN KONTROL KEPENDUDUKAN NEGARA: PERSPEKTIF GEOGRAFI POLITIK ATAS BONUS DEMOGRAFI DAN KETIMPANGAN SPASIAL DI INDONESIA - Husna Amalia Zahra; Cynara Salsabila Fatoni; Ikhsan Maulana; Melodia Ainun Nazibah (Jurnal Geografi, 2026)
Fertility policy is one of the tools used by the state to control population growth and support national development. This study aims to analyze fertility policy in Indonesia from a political geography perspective, particularly in relation to the demographic bonus and inequality between regions. The method used is a descriptive qualitative approach through literature review and documentation collection. The research findings indicate that fertility policy focuses not only on regulating birth rates but also on improving population quality and regional development. Currently, Indonesia is experiencing a demographic bonus phase that offers opportunities for economic growth through the dominance of the productive-age population. However, exploiting this opportunity still faces various challenges such as unemployment, educational inequality, and limited access to reproductive health services. Furthermore, there are differences in fertility rates across regions, with urban areas having lower fertility rates compared to peripheral areas such as Papua and East Nusa Tenggara. Therefore, a population policy that is equitable and appropriate to the characteristics of each region is needed to ensure that the demographic bonus can be managed most effectively and sustainably.